A new species of the genus Sarsamphiascus Huys, 2009 (Copepoda: Harpacticoida: Miraciidae) from a sublittoral zone of Hawaii - Jisu Yeom; Wonchoel Lee (PeerJ, 2020)
A new species of Sarsamphiascus Huys, 2009 was collected from sandy sediments of Hawaii at 12 –18 m depth. While the new species, Sarsamphiascus hawaiiensis sp. nov., is morphologically most closely related to S. kawamurai (Ueda & Nagai, 2005), the two species can be distinguished by the combination of the following morphological characteristics: elongated segments of the antennule in the new species, type of outer setae of the P5 exopod (bare in S. kawamurai), position of the inner seta of the P5 exopod in both sexes (more proximal in S. kawamurai), length and type of the setae of female P6 (shorter and bare in S. kawamurai). This is the first species of Sarsamphiascus from Hawaii to be discovered. Molecular analyses of mitochondrial cytochrome c oxidase subunit I (mtCOI) and nuclear 18S ribosomal RNA (18S rRNA) genes confirmed that S. hawaiiensis and S. kawamurai are distinct species.